International Development Agenda in Resolutions of General Assembly and ECOSOC of the United Nations from 1946 to 2000 - Alexander Alexandrovich Ignatov (Vestnik RUDN International Relations, 2019)
The United Nations established after the Second World War by the winner countries was a key institution which formed the conceptual basis for international development possessed all necessary instruments and knowledge for its implementation in concrete countries. The paper explores a role of two main UN bodies - General Assembly (UN GA) and Economic and Social Council (ECOSOC) in forming and pushing international development from the Organization establishment and till adoption of the Millennium Development Goals (MDGs) in 2000. To implement this research task the authors apply content-analysis and comparative historical analysis methods. A special database of the UN GA and ECOSOC documents dated 1946-2000 devoted to the development issues was made as well. The authors come to a conclusion that at the initial stage (1946-1959) both the UN GA and ECOSOC handled the similar tasks aimed at creating a new system of development institutions. After the adoption in 1961 the first Development Decade by the UN and till 2000 a process of division of powers of two bodies started. During this period a share of program documents in the GA discourse increased that laid a foundation for adoption by the global community the MDGs in 2000, operational and organizational issues were absorbed by the ECOSOC. The UN General Assembly was an important platform for the international dialogue on development which made it possible for the global community to adopt the Millennium Development Goals and Sustainable Development Goals (SDGs) in the 21st century. The UN GA acted as a catalyzing power for inclusion of new development issues in the agenda and creations of instruments and mechanisms for their implementation. The ECOSOC played a technical and coordinating role in a process of elaborating the international development agenda.